KAJIAN METAKOGNITIF: PEMBELAJARAN MENULIS ESAI DALAM ARTIKEL JURNAL - Yundiani, Sri; Andini, Natasya Maulida; Ilma, Anwar (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2023)
Learning to write is a productive and expressive skill. The purpose of this research is to examine journal articles in the field of essay writing as input for planning to write new journal articles. The research method uses a qualitative descriptive method. The research technique uses three data analysis techniques, namely content analysis, document analysis, and metacognitive. The data sources used in this writing are three Indonesian-language journal articles about learning to write essays. The three journal articles are by Abdul Haliq and Akmal Hamsa (2021). With the title Digital Literacy: Level and Reliability of Student Reference Resources in Writing Academic Essays, Umm Rosyidatul (2019) entitled Learning to Write Essays Using a Contextual Approach and Video Media in Class XI SMA Darul 'Ulum Sugio, and journal articles written by Ade Eka Anggraini and Elih Solihatulmilah (2020) entitled Improving Indonesian Essay Writing Skills Through Modelling Strategies. The results of this study found that in the three journal articles studied, there were two core approaches, namely qualitative methods and mixed methods (qualitative and quantitative), and then there were three patterns that could be used to create new research designs, namely: replication, modification, or developing patterns based on models from previous studies. Keyword: writing, metacognitive, essay